2008
DOI: 10.1007/s10499-008-9204-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of freshwater pearl mussel (Hyriopsis cumingii) in populations from the five largest lakes in China revealed by inter-simple sequence repeat (ISSR)

Abstract: Triangle sail mussel (Hyriopsis cumingii) is the most important mussel species commercially exploited for freshwater pearl culture in China. Its genetic diversity was studied among populations from the five largest freshwater lakes of China, Poyang Lake (PY), Dongting Lake (DT), Taihu Lake (TH), Hongze Lake (HZ), and Chaohu Lake (CH), by the polymorphism of the inter-simple sequence repeats (ISSRs). Polymerase chain reaction (PCR) detections showed that a total of 62 loci were amplified from eight primers; of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
(19 reference statements)
2
6
0
Order By: Relevance
“…To our knowledge, these are the first genotype data obtained for CNVs in freshwater bivalves. Our finding that there were more copy number variations in the wild population than in the cultured population is in agreement with other results obtained by simple sequence repeats and other markers in our laboratory [18], [48]. In the wild population, seven, eight, nine, and 10 copy number variations were the principal genotypes, which suggested the mussels with higher copy number in ferritin would be easier to survive in lake, and implied that ferritin dosage may convey a growth or resistance advantage.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, these are the first genotype data obtained for CNVs in freshwater bivalves. Our finding that there were more copy number variations in the wild population than in the cultured population is in agreement with other results obtained by simple sequence repeats and other markers in our laboratory [18], [48]. In the wild population, seven, eight, nine, and 10 copy number variations were the principal genotypes, which suggested the mussels with higher copy number in ferritin would be easier to survive in lake, and implied that ferritin dosage may convey a growth or resistance advantage.…”
Section: Discussionsupporting
confidence: 93%
“…As compared with RAPD markers, a larger number of loci/ fragments can be produced more rapidly with a limited number of primers to estimate the genetic diversity in a population. In a recent, study of Trachidermus fasciatus, it is reported that ISSRs are good DNA markers for diversity studies and furthermore the genetic differences in the hatchery populations are low as compared to wild populations (Li et al, 2009). These results were although for endangered fish species from China, but they verified the present finding about the genetic diversity of L. rohita, C. catla and their hybrids from hatchery stocks.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the amplified loci ranged from 250bp to 1500bp which are in good agreement of previous ISSR studies. Li et al (2009) (Table 1). This low genetic variation may be due to inbreeding practices usually carried out at fish seed hatcheries.…”
Section: Discussionmentioning
confidence: 99%
“…Systematics of duckweed was classified according to the method of E. Landolt et al [3] and the number of populations and accessions was as following [23,[26][27][28][29][30]: 16 populations were from five species of genus Lemna and 11 populations from two species of genus Spirodela. Five Lemna species, Lemna minuta, Lemna minor, Lemna aequinoctialis, L. gibba, Lemna perpusilla, had 3, 5, 3, 3, 2 populations, respectively.…”
Section: Plant Materialsmentioning
confidence: 99%